More frequent commitments promote cooperation, ratcheting does not - Axel Ockenfels; Carlo Gallier; Bodo Sturm (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
International climate negotiations have so far failed to produce ambitious climate cooperation. We combine laboratory experiments with simulations to investigate the performance of two negotiation design features to address this failure: The Paris Agreement's ratchet-up mechanism, which requires countries to gradually increase their ambition, and a new policy proposal to negotiate more frequently. We find that more frequent interactions allow subjects to build trust and cooperation more safely over time. Conversely, subjects in a ratchet-up design tend to become more cautious to protect themselves from free riders. Thus, more frequent revisions of commitments promote cooperation, but the ratchet-up design fails to achieve the same result.
Keywords: C72; C91; C92; D02; H41; Q54; 330; Climate change; climate negotiations; cooperation; laboratory experiments; simulations